(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
In the article "How do we perceive the world?" of the subject "Computer Science and Information Technology", taught to first-graders from the 2023-2024 academic year. In teaching the chapter called "Mind Map", the possibilities of developing the imagination and full-fledged thinking of first-graders were studied. It has been shown that the use of mind maps in education can help students develop not only logical thinking skills, but also "out-of-the-box thinking" skills that can give people an advantage over robots. The "Imagination" mind map shows the perception of information received from the outside world in the right hemisphere of the brain and the formation of imagination based on it. The article presents methods for developing students’ imagination and critical thinking skills using the "Sensory Channels" and "Seasons" mind maps. These mind maps, which are published for the first time, show that students can gain knowledge about the world around us and the changes occurring in it, their impact on our senses, compare them, identify their similarities and differences, what emotions they evoke, and the skills of thinking about them